2021
DOI: 10.3390/pathogens10030312
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Doxycycline on Replication of Feline Coronavirus

Abstract: Feline infectious peritonitis (FIP) is a sporadic fatal disease of cats caused by a virulent variant of feline coronavirus (FCoV), referred to as FIP virus (FIPV). Treatment options are limited, and most of the affected cats die or are euthanized. Anecdotally, doxycycline has been used to treat FIP-affected cats, but there are currently no data to support or discourage such treatment. The aim of this study was to establish whether doxycycline inhibits replication of FIPV in vitro. The virus was cultured in Cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…( Dunowska and Ghosh, 2021 , Bivins et al, 2020 , Chinese Center for Disease Control and Prevention, 2020 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…( Dunowska and Ghosh, 2021 , Bivins et al, 2020 , Chinese Center for Disease Control and Prevention, 2020 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…A combination of ITZ with prednisolone, ITZ with GS-441524, and ITZ with an anti-human TNF-alpha monoclonal antibody have been reported [ 27 , 28 ]. Doxycycline, a tetracycline-class antibiotic that includes other activities such as anti-inflammatory, anti-apoptotic, antivirus effects, and matrix metalloproteinase inhibition, has been used to treat cats affected by FIP [ 29 , 30 ]. Dunowska and Ghosh [ 30 ] reported that doxycycline has some inhibitory effects on FIPV replication in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline, a tetracycline-class antibiotic that includes other activities such as anti-inflammatory, anti-apoptotic, antivirus effects, and matrix metalloproteinase inhibition, has been used to treat cats affected by FIP [ 29 , 30 ]. Dunowska and Ghosh [ 30 ] reported that doxycycline has some inhibitory effects on FIPV replication in vitro . However, further studies should be conducted in vivo to evaluate its efficacy on FIP cats [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation